2017
DOI: 10.1177/1082013217734089
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the survival of Salmonella Enteritidis and Salmonella Typhimurium during the fermentation of yogurt

Abstract: The objective of this study was to evaluate the behavior of Salmonella Enteritidis and Salmonella Typhimurium, the two most important serovars of salmonellosis , during the fermentation of yogurt. The microorganisms were enumerated in milk throughout the fermentation process at three initial inoculum levels (3, 5 and 7 log CFU/mL). DMFit software was used in the fitting procedure of the data (IFR, Norwich, UK, Version 3.5). The data provided sigmoidal curves that were successfully displayed with the Baranyi mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Foodborne pathogens pose a significant threat to world healthcare and a considerable economic burden. Some foodborne pathogens can survive the fermentation and storage processes (Savran, Pérez‐Rodríguez, & Halkman, ). Previous reports identified antibiotic‐resistant bacterial strains (Milazzo, Speciale, Musumeci, Fazio, & Blandino, ; Temmerman, Pot, Huys, & Swings, ) and undesirable fungal contaminants (Lee et al, ; Motawee & Neveen, ) in fermented food products.…”
Section: Discussionmentioning
confidence: 99%
“…Foodborne pathogens pose a significant threat to world healthcare and a considerable economic burden. Some foodborne pathogens can survive the fermentation and storage processes (Savran, Pérez‐Rodríguez, & Halkman, ). Previous reports identified antibiotic‐resistant bacterial strains (Milazzo, Speciale, Musumeci, Fazio, & Blandino, ; Temmerman, Pot, Huys, & Swings, ) and undesirable fungal contaminants (Lee et al, ; Motawee & Neveen, ) in fermented food products.…”
Section: Discussionmentioning
confidence: 99%
“…(YANG et al, 2020). SAVRAN et al (2018) demonstrated the survival capacity of this bacterium during the fermentation of milk, even with a low level of initial contamination, demonstrating that factors related to the survival capacity of S. Typhimurium may also favor the occurrence of cases and outbreaks involving the microorganism.…”
Section: Lima Et Almentioning
confidence: 95%
“…The priority task facing the livestock industry of the Republic of Kazakhstan is to ensure a high level of milk productivity of cattle and produce milk of high sanitary and technological quality. Bacillus and Lactobacillus are able to acidify the environment, and are antagonists of a number of microorganisms such as Salmonella , Proteus , Staphylococcus , Escherichia coli , pseudomonads, aeromonads, streptococci, yeast fungi, etc., with the help of producers, and also synthesize amino acids and vitamins [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%